The Commodification of Academic Research : Science and the Modern University - Radder, Hans (Book collections on Project MUSE., 2010)
"The epistemic and moral responsibilities of universities, whether for-profit or nonprofit, are examined from several philosophical standpoints. The contributors discuss the pertinent epistemological and methodological questions, the sociopolitical issues of the organization of science, the tensions between commodified practices and the ideal of "science for the public good," and the role of governmental regulation and personal ethical behavior. The contributors consider alternatives to the coercive and corruptive influences of academic commodification, and offer practical recommendations for establishing appropriate research standards, methodologies, and institutional arrangements and a corresponding normative ethos."--BOOK JACKET.